Stimulating Sunscreen Use Among Outdoor Construction Workers: A Pilot Study - Keurentjes, Anne J.; Kezic, Sanja; Rustemeyer, Thomas; Hulshof, Carel T. J.; van der Molen, Henk F. (Frontiers in Public Health, 2022)
Background Outdoor workers (OW) receive a higher dose of ultraviolet radiation (UVR) compared to indoor workers (IW) which increases the risk of non-melanoma skin cancer (NMSC). Regular sunscreen use reduces the NMSC risk, however, adequate sun-safety behavior among OW is poor. The main objective was to conduct method- and intervention-related elements of a future intervention trial among OW, based on providing sunscreen and assessing sunscreen use on group- and individual level. Methods This pilot study was conducted at a construction site in the Netherlands from May-August 2021. Nine dispensers with sunscreen (SPF 50+) were installed at the worksite. OW (n = 67) were invited to complete two (cross-sectional) questionnaires on sun-safety behavior, before and after providing sunscreen. Stratum corneum (SC) samples for the assessment of UV-biomarkers were collected from the forehead and behind the ear from 15 OW and 15 IW. The feasibility of the following elements was investigated: recruitment, (loss to) follow-up, outcome measures, data collection, and acceptability of the intervention. Results The first questionnaire was completed by 27 OW, the second by 17 OW. More than 75 percent of the OW were aware of the risks of sun exposure, and 63% (n = 17) found sunscreen use during worktime important. The proportion of OW never applying sunscreen in the past month was 44.4% (n = 12) before, and 35.3% (n = 6) after providing sunscreen. A majority of OW (59.3%, n = 16) found sunscreen provision encouraging for sunscreen use, the dispensers easy to use (64.7%, n = 17) and placed in practical spots (58.8%, n = 18). Collecting SC-samples was fast and easy, and several UV-biomarkers showed higher levels for sun-exposed compared to less exposed body parts. There was no significant difference in UV-biomarker levels between OW and IW. Conclusions This pilot study revealed low sunscreen use among OW despite providing sunscreen, overall satisfaction with the sunscreen, and the sufficient awareness of the risks of UVR-exposure. Collecting SC-samples at the workplace is feasible and several UV-biomarkers showed to be promising in assessing UVR-exposure. The low participation rate and high loss to follow-up poses a challenge for future intervention studies.